Does procedural justice climate increase the identification and engagement of migrant workers? A group engagement model perspective. Issue 1 (10th November 2020) - Adamovic, Mladen; Gahan, Peter; Olsen, Jesse; Harley, Bill; Healy, Joshua; Theilacker, Max
Abstract : Purpose: Migrant workers often suffer from social exclusion in the workplace and therefore identify less with their organization and engage less with their work. To address this issue, the authors integrate research on migrant workers with research on the group engagement model to create a model for understanding and enhancing migrant worker engagement. This allows us to provide insight into how organizations can design their human resource management systems and practices to increase the work engagement of migrant workers. Design/methodology/approach: The authors conducted a survey study with over 4, 000 employees from more than 500 workplaces in Australia to test the model. Findings: The results of the multilevel analysis indicate that a procedurally fair work environment increases organizational identification, which in turn is associated with higher work engagement. The results also indicate that procedural justice climate is more important for migrant workers and increases their organizational identification and engagement. Originality/value: To increase work engagement of migrant workers, organizations can establish a procedurally fair work environment in which cultural minorities experience unbiased policies and procedures, are able to express their opinions and participate in decision-making.